Picky eating in an obesity intervention for preschool-aged children - what role does it play, and does the measurement instrument matter? - Pernilla Sandvik; Anna Ek; Karin Eli; Maria Somaraki; Matteo Bottai; Paulina Nowicka (BMC, 2019)
Abstract Introduction Research on picky eating in childhood obesity treatment is limited and inconsistent, with various instruments and questions used. This study examines the role of picky eating in a randomized controlled obesity intervention for preschoolers using subscales from two instruments: The Child Eating Behavior Questionnaire (CEBQ) and the Lifestyle Behavior Checklist (LBC). Method The study includes 130 children (mean age 5.2 years (SD 0.7), 54% girls, mean Body Mass Index (BMI) z-score 2.9 (SD 0.6)) and their parents (nearly 60% of non-Swedish background, 40% with university degree). Families were randomized to a parent-group treatment focusing on evidence-based parenting practices or to standard treatment focusing on lifestyle changes. The children's heights and weights (BMI z-score) were measured at baseline, and at 3, 6 and 12 months post baseline. At these time-points, picky eating was reported by parents using the CEBQ (Food Fussiness scale, 6 items) and 5 items from the LBC. Child food intake was reported with a Food Frequency Questionnaire (FFQ). Pearson correlation was used to study associations between baseline picky eating and baseline BMI z-scores and food intake. Mixed effects models were used to study associations between the two measurements of picky eating and changes in picky eating, to assess the effects of changes in picky eating on BMI z-scores, and to evaluate baseline picky eating as a predictor of changes in BMI z-scores. Results Neither the standard treatment nor the parent-group treatment reduced the degree of picky eating (measured with CEBQ or LBC). Baseline picky eating measured with the CEBQ was associated with a lower BMI z-score and lower intake of vegetables. Children with a higher degree of picky eating at baseline (measured with the CEBQ) displayed a lower degree of weight loss. When degree of picky eating was examined, for 25% of the children, the CEBQ and the LBC yielded diverging results. Conclusions Baseline picky eating may weaken the effectiveness of obesity treatment, and assessments should be conducted before treatment to adjust the treatment approach. Different measurements of picky eating may lead to different results. The CEBQ seems more robust than the LBC in measuring picky eating. Trial registration Clinicaltrials.gov, NCT01792531. Registered 15 February 2013 - Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT01792531